Screening the human mind: A Deleuzian approach to altered states of consciousness in cinema history: Toward an idea of the virtual image in the cinema (II) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
From its very origins, cinema has demonstrated a particular interest in the representation of altered states of consciousness: memories, visions, nightmares and dreams are a common feature of narrative films and usually interrupt a flow of events by inserting different temporalities in the present of the story. Following the arguments explored by Gilles Deleuze in his groundbreaking works on cinema, this essay will address the issue of how narrative cinema has represented altered states of consciousness. If in early cinema of attractions altered states were represented as physical realities intertwined with the world, classical Hollywood films progressively exorcised the disruptive potential of such images by defining a visual grammar in order to normalize them within the narrative. It will be modern cinema which will focus on this issue in depth, given its new interest in the link between the moving image and the mechanisms of thought. In this regard, the essay will in conclusion address the hallucinations experienced by Isak Borg in Bergman’s Wild Strawberries, a complex and highly illuminating case of various forms of altered mental states.
Keywords: Deleuze; Cinema; Temporality; Hallucination; Bergman